1995
DOI: 10.1016/0168-1702(95)00006-c
|View full text |Cite
|
Sign up to set email alerts
|

The membrane glycoprotein G1 of Uukuniemi virus contains a signal for localization to the Golgi complex

Abstract: Members of the Bunyaviridae family acquire their envelopes by budding into the Golgi complex (GC). The accumulation of the membrane glycoproteins G1 and G2 in the GC probably determines the site of maturation. Here we have studied the intracellular transport and targeting to the GC of G1 and G2 of Uukuniemi virus, a member of the Phlebovirus genus, and report on their expression from cloned cDNAs either together or separately by using a T7 RNA polymerase-driven vaccinia virus expression system. When G1 and G2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
33
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 41 publications
6
33
0
Order By: Relevance
“…None of the MAbs detected G N or G C protein on the surfaces of unpermeabilized cells (data not shown). Our results indicate that the CCHFV glycoproteins are not delivered to the cell surface in appreciable quantities, which is consistent with studies that have shown that other Bunyaviridae bud into the Golgi apparatus and that their glycoproteins are targeted to this organelle and not delivered to the cell surface (13,18,29,34,37).…”
Section: Resultssupporting
confidence: 78%
“…None of the MAbs detected G N or G C protein on the surfaces of unpermeabilized cells (data not shown). Our results indicate that the CCHFV glycoproteins are not delivered to the cell surface in appreciable quantities, which is consistent with studies that have shown that other Bunyaviridae bud into the Golgi apparatus and that their glycoproteins are targeted to this organelle and not delivered to the cell surface (13,18,29,34,37).…”
Section: Resultssupporting
confidence: 78%
“…As was found for the animal-infecting bunyaviruses Uukuniemi virus (27,32) and Bunyamwera virus (23), the N-terminal protein G2 of the TSWV glycoprotein precursor could be transported to the Golgi system on its own, though with decreased efficiency, and apparently contains a Golgi retention signal. The C-terminal protein G1 expressed on its own was unable to leave the ER and thus seems to require an interaction with G2 in order to be transported out of the ER.…”
Section: Discussionmentioning
confidence: 97%
“…We recently mapped the signal for Golgi targeting and retention to the transmembrane domain of Gn (46). The requirement for Gn-Gc heterodimerization for efficient trafficking to the Golgi has also been documented for other members of family, such as Uukuniemi, Punta Toro and Rift Valley Fever viruses of the Phlebovirus genus (9,17,31,40), La Crosse virus of the Orthobunyavirus genus (6), Hantaan and Sin Nombre viruses of the Hantavirus genus (42,45,47), and tomato spotted wilt virus of the Tospovirus genus (23).…”
mentioning
confidence: 99%